Multiply imaged time-varying sources behind galaxy clusters: comparing fast radio bursts to QSOs, SNe, and GRBs - Wagner, Jennifer; Liesenborgs, Jori; Eichler, David (Astronomy and astrophysics, 2019)
With upcoming (continuum) surveys of high-resolution radio telescopes, detection rates of fast radio bursts (FRBs) might approach 105 per sky per day by future extremely large observatories, such as the possible extension of the Square Kilometer Array (SKA) to a phase-2 array. Depending on the redshift distribution of FRBs and using the repeating FRB121102 as a model, we calculate a detection rate of multiply imaged FRBs with their multiply imaged hosts caused by the distribution of galaxy-cluster-scale gravitational lenses of the order of 10−4 per square degree per year for a minimum total flux of the host of 10 μJy at 1.4 GHz for SKA phase 2. Our comparison of estimated detection rates for quasars (QSOs), supernovae (SNe), gamma ray bursts (GRBs), and FRBs shows that multiple images of FRBs could be more numerous than those of GRBs and SNe and as numerous as multiple images of QSOs. Time delays between the multiple images of an FRB break degeneracies in model-based and model-independent lens reconstructions as other time-varying sources do, yet without a microlensing bias, as FRBs are more point-like and have shorter duration times. We estimate the relative imprecision of FRB time-delay measurements to be 10−10 for time delays on the order of 100 days for galaxy-cluster-scale lenses, yielding more precise (local) lens properties than time delays from the other time-varying sources. Using the lens modelling software Grale, we show the increase in accuracy and precision of the reconstructed scaled surface mass density map of a simulated cluster-scale lens when adding time delays for one set of multiple images to the set of observational constraints.
Gesehen am 11.12.2019